Decision making models in nursing - Kosicka, Bogumiła; Ksykiewicz-Dorota, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2008)
In modern nursing the role of professional autonomy and responsibility of the nurse is stressed. In nursing practice autonomy is understood as the right to decide about the elements of patient care and being responsible for the result of one’s actions. Decision making lies at the basis of today’s and future nursing, so a careful study of the subject seems necessary. The aim of the dissertation is to show the decision making models in nursing practice on the basis of avaible literature. This dissertation presents ones of the most significance different models of decision from the nursing point of view. Research showed that the models of decision making in nursing, as described in literature, can be grouped in two broad categories: first group consisting of the rational, linear, gradual and scientific decision making process; the latter one described as intuitive, reflexive activity based mostly on personal characteristics of the deciding person. The analysis led us to isolation of the following models of decision making in nursing: — analytical model, — data processing model (hypothetical-deductive), — procedural model, — intuitive model, — analytical-intuitive model. The decision making process requires both analytical and intuitive model of decision making, depending on the nursing situation and stage of the process itself.